The effectiveness of bupivacaine infiltration during thyroid surgery for postoperative analgesia - Yasar, M.A.; Erdogan, M.; Ozmis, M.; Akkus, M.A.; Erhan, O.L. (My University, 1997)
The efficacy of analgesia using bupivacaine 0,5% wound infiltration for thyroid surgery was evaluated with regard to pain scores and 24 hours postoperative pethidine demand. Group I consisted of patients receiving bupivacaine 0,5% (10 ml) wound infiltration immediately before skin closure and group II consisted of patients without infiltration. All patients received the same anaesthesia including thiopental, vecuronium, O2/N2O and isoflurane. Postoperative pain medication included pethidine IM, as needed. 24 hours after surgery pethidine requirement and the worst pain scores were recorded. Pain scores and pethidine requirement significantly decreased in group I (p<0,05). We concluded that our study demonstrates a simple, effective and safe way to decrease pain following thyroid surgery.
Tiroid cerrahisinde uygulanan bupivakain infiltrasyonunun postoperatif analjezik etkinligi
Keywords: bupivacaine; postoperative analgesia; thyroidectomy